2005
DOI: 10.1149/1.1979214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carboxymethyl Cellulose on Aqueous Processing of Natural Graphite Negative Electrodes and their Electrochemical Performance for Lithium Batteries

Abstract: Suspensions of natural graphite particles were prepared in an aqueous medium using carboxymethyl cellulose ͑CMC͒ and emulsified styrene-butadiene copolymer latex as part of an environmentally friendly fabrication process for graphite anodes ͑negative electrodes͒ intended for application in Li-ion batteries. Suspensions were characterized by adsorption isotherms, electroacoustic measurements, rheology and sedimentation tests, at two different degrees of carboxymethyl substitution ͑DS͒ on CMC. A lower DS value ͑… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
129
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 205 publications
(131 citation statements)
references
References 16 publications
0
129
1
1
Order By: Relevance
“…It was reported that by varying levels of carboxymethyl (-OCH 2 COO -Na + ) substitution, the adhesion of active materials to a copper current collector and the dispersion of the electrode slurry can be controlled [28]. Munao et al demonstrated that the aggregation of PVDF binder and Si particles was more severe compared to a CMC-Si electrode; thus, the PVDF-Si electrode loses its electrical conduction network [29].…”
Section: Homopolymersmentioning
confidence: 99%
“…It was reported that by varying levels of carboxymethyl (-OCH 2 COO -Na + ) substitution, the adhesion of active materials to a copper current collector and the dispersion of the electrode slurry can be controlled [28]. Munao et al demonstrated that the aggregation of PVDF binder and Si particles was more severe compared to a CMC-Si electrode; thus, the PVDF-Si electrode loses its electrical conduction network [29].…”
Section: Homopolymersmentioning
confidence: 99%
“…The DS indicates the average number of carboxymethyl groups attached to the glucose unit. A low DS usually provides better performance because of additional interactions between NaCMC and graphite [40]. For this study, it has been decided to use NaCMCs with a low degree of substitution, ranging from 0.7 to 0.8.…”
Section: Battery Cyclingmentioning
confidence: 99%
“…Many studies have indicated that water processable cellulose-like materials may be suitable binders for both anode and cathode. 10,19,21,22 The use of carboxymethylcellulose (CMC) as binder for a graphitebased anode material was first described by Lee et al 23 CMC binder has been proposed also for Si-based electrodes. It can promote the formation of a stable solid electrolyte interface (SEI) layer by acting as a surface modifier and can facilitate networking between the conductive carbon and the Si particles because of its extended structure.…”
mentioning
confidence: 99%